Two-Dimensional Photoacoustic/Ultrasonic Endoscopic Imaging Based on a Line-Focused Transducer - Pang, Weiran; Wang, Yongjun; Guo, Lili; Wang, Bo; Lai, Puxiang; Xiao, Jiaying (Frontiers in Bioengineering and Biotechnology, 2022)
Existing acoustic-resolution photoacoustic/ultrasonic endoscopy (PA/USE) generally employs a point-focused transducer for ultrasound detection, which is only sensitive in its focal region, thus the lateral resolution and sensitivity drop dramatically when the targets move far from its focus. Even if a dynamic focusing algorithm is applied, the sensitivity out of the transducer focus is still much lower than that in the focus in ultrasonic imaging mode. In this work, we propose an acoustic-resolution PA/USE with a line-focused transducer to realize automatic focusing for the first time. In comparison to a point-focused transducer, the line-focused transducer emits a more uniform sound field, causing the original signal intensity and signal-to-noise ratio (SNR) of the front and rear targets to be closer in the radial direction, which is beneficial for improving target signal uniformity in ultrasonic imaging. Simultaneously, we improved the resolution of the defocus area by modifying a prior work of back-projection (BP) reconstruction algorithm typically used in point-focused transducer based PAE and applying it to line-focused PA/USE. This combined approach may significantly enhance the depth of field of ultrasonic imaging and the resolution of the defocus zone in PA/US imaging, compared to the conventional method. Sufficient numerical simulations and phantom experiments were performed to verify this method. The results show that our method can effectively improve the lateral resolution in the image’s defocused region to achieve automatic focusing and perfectly solve the defect of the target signal difference in the far-focus region in ultrasonic imaging, while also enhancing the image SNR and contrast. The proposed method in this paper lays foundations for the realization of photoacoustic/ultrasonic combined endoscopy with enhanced lateral resolution and depth of field, which can potentially benefit a many of biomedical applications.